Retrospective Study of Magnetic Resonance Imaging (MRI) Findings in Pott’s Spine - Ghazala Wahid, Sayed Sohail Akhtar, Ayesha Kamran, Mehvish Zahra Alavi, Nadia Haider, Maria Musammar (Pakistan Journal of Medical & Health Sciences, 2022)
Tuberculosis is the very communal infection found globally and can nearly all parts of the human body can be affected by it, mostly affect the chest. Among the tuberculosis of the skeletal system; 50% of cases affect the spinal cord. Tuberculosis infection of the spinal cord results in Gibbus deformity, edema, involvement of intervertebral discs, epidural abscess, paravertebral abscess and edema with bone destruction and vertebrae collapse in the soft tissue planes. The most valuable diagnostic tool is MRI as it can clearly show all of the above results in the spine tuberculosis affected patients. Aim: The objective of this research was to know the pattern of incidence and to analyzed the several Pott’s spine pathological processes by means of the MRI scan. Study Design: A Retrospective study. Place and Duration: In the Radiology Department of HMC Peshawar and Orthopedic Department of BKMC Swabi from August 2021 to January 2022. Methods: This study analyzed MRI scans of 90 identified patients of spinal tuberculosis performed at the Radiology Department to govern the pattern of the several pathological lesions. Results: This study institute Pott’s spine to be more common in the 21-50 age group, mostly among men. The lumbar and dorsal vertebrae are often affected and several vertebrae are affected frequently, with the most common affected is the L3 vertebra. The involvement of Intervertebral disc and para and pre-vertebral collections were communal, with epidural collection happening in > 75 of patients. 13.3% of the patients have cord oedema. Conclusions: MRI is very sensitive in detecting various Potts spine pathological processes, and the occurrence patterns of these findings were assessed in this research. As the prevalence and incidence of tuberculosis depends on several sensitive epidemiologically parameters, this research could deliver a standard conclusion against which further results could be compared in future studies. Keywords: Tuberculous spondylitis, lumbar abscess, Gibbus